The impact of anxiety on Chinese as a second language achievement: a meta-analytic perspective - Qiao, Peng; Yuan, Zhicheng; Li, Shuhong (Frontiers in Psychology, 2025)
In light of the growing global enthusiasm for learning Chinese, understanding the psychological factors influencing Chinese language learners—particularly the impact of anxiety on second language Chinese achievement (hereafter “Chinese achievement”)—is essential for improving teaching effectiveness. However, the specific effects and magnitude of this relationship remain a topic of academic debate. Grounded in the Control-Value Theory, this study employs a meta-analytic approach to synthesize findings from 23 empirical studies, encompassing 58 independent effect sizes and a total of 4,191 participants. The results reveal a small-to-moderate negative correlation between anxiety and Chinese achievement. Moderator analyses indicate that language proficiency level and the proportion of female learners significantly influence this relationship. Specifically, the negative impact of anxiety is most pronounced among beginners, followed by advanced, intermediate, and mixed-proficiency learners. Additionally, anxiety has a stronger detrimental effect on Chinese achievement in learner groups with a higher proportion of females. However, publication language, participant region, learning context, language skills, and achievement measurement did not exhibit significant moderating effects. These findings provide valuable implications for international Chinese language education, highlighting the importance of a student-centered teaching approach, optimized instructional strategies, and enhanced teaching quality.